Undoing gender inequalities: insights from the Portuguese perspective - Schouten, Maria Johanna Christina (2019)
In Portugal and elsewhere in the world, the movement promoting gender equality has known advances and setbacks over the past century. While acknowledging and outlining the major favourable developments, this paper discusses mainly some tendencies in the opposite direction, in particular those that highlight and encourage, from an early age, differences between men and women, usually to the detriment of the latter. Examples in Portugal include the growing genderization of children’s toys and books (which in one case has triggered a widely-mediatized polemic in September 2017) and the importance of the colours pink and blue. After childhood, differences persist regarding choice of study, professional activities, salary and domestic responsibilities. In this respect, sociological research in Portugal has observed a backlash in the position of women, in particular as an effect of the financial and economic crisis in the period 2010-2014.